Strategi Guru dalam Meningkatkan Kemampuan Berfikir Kritis Siswa Kelas VII melalui Model Pembelajaran Berbasis Keterampilan di MTs. NW Selebung Ketangga - Gapari, Muhamad Zaril (AS-SABIQUN, 2025)
All children basically need education because education allows them to identify their interests and talents. Both formal and informal institutions can foster these interests and abilities. This study aims to determine how teachers implement skill-based learning strategies and improve critical thinking skills of MT. Tangga Selebung students. Through observation, interviews, and recording, the researcher used a descriptive analysis approach to collect data for this qualitative study. Triangulation procedures were used to ensure the accuracy of the researcher's data. The data analysis procedure consisted of three steps: documentation, interviews, and observation results. The principal, BK teacher, subject and class teachers, and students acted as research informants. The research findings included the identification of four different levels of language competency through interviews. Speaking, listening, writing, and reading. Students learn to recognize numbers and do addition, subtraction, and division to understand basic concepts. Some instructors use integrative and lecture techniques to help students hone their critical thinking skills. especially the lecture style, which uses oral teaching materials to tell a story about a subject, and integrative techniques, which integrate several classes into one theme. In addition, some educators use the expository method, a teacher-centered learning approach.